A framework for developing a national strategy for environmental education - M. Yassin, Sulaiman (1982)
This paper attempt to provide a basis for discussion of important considerations that should be taken into account in the initial planning and conceptualization of a national strategy for environmental education. This paper emphasizes the development of a framework that can be useful to guide the planning of necessary steps in such an exercise. In the development of the framework, several concept in system, organizational behaviour, adult education and learning theories are examined. The various outcomes envisaged for the environmental education programme, the process involved in the inputs required are further discussed. The interaction and linkage between these enabling factors are further elaborated upon viewed from the perspectives of the sosio-cultural, national development objectives and the political philosophy of the nation. Several strategies are implied in the discussion based on the proposed framework and also in the light of development trends in the ASEAN region.